A Comparison of Food-grade Folium mori Extract and 1-Deoxynojirimycin for Glycemic Control and Renal Function in Streptozotocin-induced Diabetic Rats - Shiang-Suo Huang; Yi-Hui Yan; Chien-Hui Ko; Ke-Ming Chen; Shih-Chieh Lee; Cheng-Tzu Liu (Journal of Traditional and Complementary Medicine, 2014)
Folium mori (桑葉 Sāng Yè, leaf of Morus alba L.; FM) is known to possess hypoglycemic effects, and 1-deoxynojirimycin (1-DNJ) has been proposed as an important functional compound in FM. However, the hypoglycemic activity of purified 1-DNJ has been rarely studied. It is also not known how FM and 1-DNJ affect the development of DM nephropathy. This study compared the antidiabetic effect of a commercial FM product with that of purified 1-DNJ in streptozotocin-induced diabetic rats. Seven days after induction, the diabetic rats were gavaged with FM (1, 3, 10, and 30 mg/kg/day), 1-DNJ (30 mg/kg/day), or vehicle (distilled deionized water; 2 ml/kg/day) for 7 days. All doses of FM ameliorated fasting and post-prandial blood glucose concomitantly with an increase in peripheral and pancreatic levels of insulin and improved homeostasis model assessment (HOMA-IR) in diabetic rats in a dose-dependent manner. Increased thiobarbituric acid reactive substances (TBARS) and nitrate/nitrite levels in the kidney, liver, and muscle of diabetic rats were reversed by all doses of FM. The renal function of the diabetic rats was normalized by all doses of FM, while blood pressure changes were reversed by FM at doses of 3 mg/kg and above. Moreover, most of the above-mentioned parameters were improved by FM at doses of 3 mg/kg and above to a similar extent as that of 1-DNJ. The results showed superior antidiabetic potential of the commercial FM product for glycemic control and protection against the development of diabetic nephropathy.